UTILIZATION OF SOCIOTECHNICAL APPROACHES IN THE APPLICATION OF AGRICULTURAL BIOTECHNOLOGY: A STUDY OF FARMER BEHAVIOR TOWARDS BIOENGINEERED PRODUCTS IN MAGETAN REGENCY - Heru Widyatmoko (CV. Radja Publika, 2025)
This research aims to understand the behavior of farmers in responding to bioengineering-based agricultural biotechnology products through a sociotechnical approach in Magetan Regency. This approach is used to analyze how the interaction between technology and social context affects the acceptance of innovation at the farmer level. The method used is qualitative with in-depth interview techniques, observations, and directed group discussions (FGD). The results of the study show that farmers' perception of bioengineered products is greatly influenced by the level of knowledge, experience, and social influence of farmer group figures. The information received by farmers tends to be minimal and biased, especially due to the weak role of agricultural extension workers and the dominance of private distributors in the delivery of information. In addition, local cultural norms and values also shape farmers' attitudes towards technology that is considered unnatural. The sociotechnical approach has proven to be able to be a bridge between technology and the social needs of farming communities, by emphasizing participatory involvement and two-way communication. Therefore, the application of agricultural technology must take into account social structures and local values to guarantee the success and sustainability of its adoption.